Heat transfer and mass transfer in simulated solar-heated membrane distillation - Fernandez, Benedicto A.
Membrane Distillation (MD) is a relatively new separation method to process aqueous solutions. It has a great potential because of its low operating temperature and pressure, its high rejection rate of non-volatile solutes in the permeate solution and its ability to keep the resulting concentrated feed solution free from chemical degradation associated with intense heat.